Understanding Islamic Media Ideology: An Analysis of the News Framing on Christmas Celebrations and Its Relation to Religious Moderation - Sunaryanto, Sunaryanto; Syamsuri, Ahmad Rofi (Jurnal Ilmiah Syi'ar, 2023)
This research aims to analyze ideology in news about Christmas celebrations and its association to religious moderation in the Hidayatullah and Eramuslim media. This research uses qualitative research with a constructivism paradigm. In the constructivism paradigm, news is not analyzed objectively based on true or false numbers but based on subjective views of interpretation. The analytical method used a textual analysis of mass media with framing by Robert M. Entman. News as the object of analysis is that 3 (three) news is selected for each of the media. The research conclusion shows that the two Islamic media define the problem, look at the causes of the problem, provide moral values and recommendations for solving the problem to defend the interests of Muslims. The ideology of these two Islamic media wants to enforce Islamic law by prohibiting Christmas celebrations held by Muslims. Celebrating Christmas with Muslims for other groups is a way to embody religious tolerance but for Hidayatullah and Eramuslim, it is considered a threat to the beliefs of Muslims. In association with religious moderation, these two Islamic media have developed a framing based on a single concept, namely religious tolerance. Other concepts, including national commitment, non-violence, and accommodating local culture, are not incorporated in the Christmas celebration news.